2016
DOI: 10.18869/acadpub.jpcp.4.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Infertility Stress, Psychological Symptoms, and Quality of Life on Predicting Success Rate of IVF/ICSI Treatment in Infertile Women

Abstract: Objective: In any society, attention to physical, mental, social, and cultural health status as well as spiritual interests and providing opportunities for realization of a dynamic and healthy life is considered as the guarantee for the community health in the coming years. One of the issues that troubles the mental health of some people is infertility. In this regard, this study aims to determine the effects of infertility stress, mental symptoms, and quality of life of infertile women on predicting success r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
1
8
0
2
Order By: Relevance
“…Finally, no significant relationship was observed between the quality of life, the cause of infertility, and the duration of infertility. In this regard, Aslzaker et al4 achieved similar results. However, in the study of Rashidi et al,2 the quality of life was reported as higher in male infertility.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Finally, no significant relationship was observed between the quality of life, the cause of infertility, and the duration of infertility. In this regard, Aslzaker et al4 achieved similar results. However, in the study of Rashidi et al,2 the quality of life was reported as higher in male infertility.…”
Section: Discussionmentioning
confidence: 75%
“…In fact, it was found that infertile women have a lower quality of life. According to Aslzaker et al4 and Andrews et al,20 high levels of stress in infertile women are related to reducing marital function and loss of quality of life, irrespective of the its reasons. Furthermore, the findings are congruent with other study results 22122.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al [4] argued that mindfulness helped infertile women to cope with IVF in adaptive manners. Additionally, Aslzaker [11] suggested that MBSR is effective in the success of IVF and psychological symptoms in women receiving IVF.…”
Section: Introductionmentioning
confidence: 99%